Intercultural communication globalization and social justice - Sorrells, Kathryn (SAGE, 2016)
aThis student introduction examines intercultural communication within the geopolitical, economic, and cultural context of globalization. It takes a social justice approach and provides a framework to create a more fair and equitable world through communication.